Selective Chemical Modification of DNA with Boronic Acids by On-Column CuAAc Reactions - Debiais, Mégane; Vasseur, Jean-Jacques; Müller, Sabine; Smietana, Michael (Synthesis, 2020)
The use of the Cu(I)-catalyzed azide–alkyne cycloaddition (CuAAC) reaction for the preparation of oligonucleotide conjugates is by now familiar. However, the selective introduction of boronic acids into DNA and RNA sequences by CuAAC reactions has long been considered impossible due to the incompatibility of the boronic acid moiety with copper salts. Here we describe two new methods for the selective on-column functionalization of oligonucleotides with boronic acids via two different CuAAC reactions. The first one allows the introduction of a phenylboronic acid at the 5′-extremity of oligonucleotides, while the selective intrastrand positioning of the modification can be achieved with the second one. Both methods were applied to the DNA and RNA series (up to a 20-mer) with good isolated yields and excellent purities. These results illustrate the potential of the reported methods for selective incorporation of boronic acids into oligonucleotides.
Keywords: CuAAc; boronic acid; oligonucleotide; bioconjugation; DNA; RNA